2011
DOI: 10.1159/000327020
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Heme Oxygenase-1 as a Sensitive Indicator of Tubulointerstitial Inflammatory Damage in Various Renal Diseases

Abstract: Background/Aims: In oxidative stress, heme oxygenase-1 (HO-1) plays a pivotal role in maintaining renal function and protecting renal structure, especially in renal tubular epithelial cells. We examined urinary HO-1 (uHO-1) levels to assess whether uHO-1 acts as a sensitive biomarker for detecting tubulointerstitial inflammatory damage in renal diseases. Methods: Immunohistochemical analyses and enzyme-linked immunosorbent assays for uHO-1 were performed using 61 urine samples (supernatants and sediment lysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…HO-1 protein excretion in urine is low or undetectable in normal humans and mice, but it was increased in humans and animals with acute kidney injury (80), another setting where RAS activation may contribute to kidney injury. 5 HO-1 protein expression was also increased in tubular cells isolated from the urine of patients with tubulointerstitial disorders (81). Finally, we found a direct linear relationship between kidney HO-1 protein expression and urine HO-1 excretion, suggesting that HO-1 excreted in urine is determined by its renal production.…”
Section: Discussionsupporting
confidence: 54%
“…HO-1 protein excretion in urine is low or undetectable in normal humans and mice, but it was increased in humans and animals with acute kidney injury (80), another setting where RAS activation may contribute to kidney injury. 5 HO-1 protein expression was also increased in tubular cells isolated from the urine of patients with tubulointerstitial disorders (81). Finally, we found a direct linear relationship between kidney HO-1 protein expression and urine HO-1 excretion, suggesting that HO-1 excreted in urine is determined by its renal production.…”
Section: Discussionsupporting
confidence: 54%
“…Either NF-κB p65 was not excreted into the urine or the molecule was too diluted within the urine to be measurable directly. Similar finding was documented for urinary haem oxygenese-1 (uHO-1) measurement, where it was undetectable in the urine supernatant [22]. Activation of NF-κB p65 has been demonstrated in glomeruli, in tubulo-interstitial cells, in infiltrating cells of obstructed kidneys [23], as well as in renal tubular cells [14].…”
Section: Discussionsupporting
confidence: 71%
“…Activation of NF-κB p65 has been demonstrated in glomeruli, in tubulo-interstitial cells, in infiltrating cells of obstructed kidneys [23], as well as in renal tubular cells [14]. The proximal and distal tubular epithelial cells were documented as major NF-κB p65 producers [22]. Recent studies show that NF-κB p65 activation has also been detected in peripheral blood mononuclear cells (PBMCs) from complicated P. falciparum malaria patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…This was felt to reflect the effects of hyperglycemia, a known pro-oxidant state. In a second study, Yokoyama et al, 27 reported that critically ill patients (e.g., after cardiac arrest) manifested increased plasma HO-1 levels. However, it is unclear how much concomitant renal injury was sustained in this patient population.…”
Section: Discussionmentioning
confidence: 96%